Pelatihan Penggunaan Running Text sebagai Media Informasi di Masjid Jami Nurul Iman Desa Jatiendah - Heri Andrianto; Dedi Anderias Bailao (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
The advancement of information technology has increasingly influenced various aspects of daily life, including the dissemination of information within places of worship such as mosques. One technological tool that can be effectively utilized for this purpose is a running text display, which can convey prayer schedules, announcements, and other relevant information in an efficient and organized manner. Jatiendah Village, located in the Cilengkrang District of Bandung Regency, is known for its devout community and active participation in religious activities. However, several mosques in the area have yet to adopt running text technology, primarily due to limited knowledge and technical skills related to its installation and operation. This community engagement initiative aimed to address this gap by providing training on the installation and use of running text displays to the management of Jami Nurul Iman Mosque in Jatiendah Village. The training methods included theoretical presentations, demonstrations, and hands-on practice. The outcomes of the program indicated that the participants successfully acquired the necessary knowledge and skills to install and operate running text systems, thereby enhancing the effectiveness of information dissemination within the mosque environment.